2020
DOI: 10.3390/pr8010105
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Active Safe Semi-Supervised Learning Framework for Fault Identification in Labeled Expensive Chemical Processes

Abstract: A novel active semi-supervised learning framework using unlabeled data is proposed for fault identification in labeled expensive chemical processes. A principal component analysis (PCA) feature selection strategy is first given to calculate the weight of the variables. Secondly, the identification model is trained based on the obtained key process variables. Thirdly, the pseudo label confidence of identification model is dynamically optimized with an historical, current, and future pseudo label confidence mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The Tennessee Eastman Process (TEP) is a commonly used benchmark in industrial and chemical engineering research and it has been thoroughly investigated in terms of process dynamics and control [39][40][41][42][43]. Recently, it has been also used to validate active learning or soft sensor modeling approaches [44][45][46][47][48]. It was initially published in 1993 [49] but since then it has been further developed and improved.…”
Section: Tennessee Eastman Processmentioning
confidence: 99%
“…The Tennessee Eastman Process (TEP) is a commonly used benchmark in industrial and chemical engineering research and it has been thoroughly investigated in terms of process dynamics and control [39][40][41][42][43]. Recently, it has been also used to validate active learning or soft sensor modeling approaches [44][45][46][47][48]. It was initially published in 1993 [49] but since then it has been further developed and improved.…”
Section: Tennessee Eastman Processmentioning
confidence: 99%
“…The variables used in this study are shown in Table 1. IDV (15) was not studied because, in previous studies conducted by Zhan et al [20], Wu et al [21], and Jia et al [27], IDV (15) is very difficult to classify. IDV (15) behavior is like IDV (0), so the program will need to diagnose no oscillation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the amount of sample data for each fault type may be unbalanced. Therefore, in order to solve the problem that the datasets are usually unlabeled and unbalanced in real situations, some scholars have adopted the semi-supervised learning (SSL) approach to fully utilize the unlabeled fault sample data for the task of fault diagnosis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%